Strategi Komunikasi Penyiar Radio Magelang FM pada Program Siaran “Mbangun Magelang” untuk Menarik Minat Pendengar - Zuanidhar, Haichal (Jurnal Pelita Teknologi, 2024)
Being in the midst of the digital era, LPPL Radio Magelang FM, which stands under the Magelang City Communication, Informatics and Statistics Service, as a mass media has certain strategies that its broadcasters use in order to maintain its existence and attract the interest of listeners through broadcast programs so that they can continues to develop in providing up-to- date information and providing cooperation with the community. Researchers used descriptive qualitative research methods through interviews, documentation and observation approaches. From the results of the research that has been carried out, the researcher can conclude that the communication strategies used by Radio Magelang FM broadcasters in attracting listeners' interest through the “Mbangun Magelang” broadcast program are strategies for determining messages, strategies for achieving effects and communication styles used in packaging broadcast programs to make them attractive to listeners.